The cerebellum is involved in implicit motor sequence learning - Firouzi, Mahyar; Baetens, Kris; Duta, Catalina; Baeken, Chris; Van Overwalle, Frank; Swinnen, Eva; Deroost, Natacha (Frontiers in Neuroscience, 2024)
BackgroundImplicit motor sequence learning (IMSL) is a cognitive function that allows us to execute multiple movements in a specific sequential order and plays a crucial role in our daily functional activities. Although the role of the basal ganglia network in IMSL is well-established, the exact involvement of the cerebellar network is less clear.AimHere, we aimed to address this issue by investigating the effects of cerebellar transcranial direct-current stimulation (tDCS) on IMSL.MethodsIn this sham-controlled, crossover study in 45 healthy young adults, we used mixed-effects models to analyze sequence-specific (primary outcome) and general learning effects (secondary outcome) in the acquisition (during tDCS), short- (five minutes post-tDCS) and long-term consolidation (one week post-tDCS) phases of IMSL, as measured by the serial reaction time (SRT) task.ResultsAnalyses based on response times (RTs) revealed that anodal tDCS over the cerebellum significantly increased sequence-specific learning during acquisition, compared to sham (anodal: M = 38.24 ms, sham: M = 26.78 ms, p = 0.032); did not affect general learning; and significantly slowed overall RTs (anodal: M = 362.03 ms, sham: M = 356.37 ms, p = 0.049). Accuracy-based analyses revealed that anodal tDCS reduced the probability of correct responses occurring in random trials versus sequential trials by 1.17%, p = 0.009, whereas sham tDCS had no effect, p = 0.999.ConclusionOur finding of enhanced sequence-specific learning, but not general learning, suggests that the cerebellar network not only plays a role in error correction processes, but also serves a sequence-specific function within the integrated motor learning network that connects the basal ganglia and cerebellum.